INCLUSION OF CORPORATE SOCIAL RESPONSIBILITY AS A MODULE IN UNIVERSITY SYLLABI: A STUDY OF CONTENTS, PEDAGOGIES AND ACADEMIA-INDUSTRY INITIATIVES IN NEPAL - Dr. Arhan Sthapit, (International Journal of Management Studies (IJMS), 2021)
The paper performs a probe into the coverage of corporate social responsibility (CSR) as a module in university syllabi in Nepal by exploring the existing CSR contents and pedagogy in the business school curricula as well as academia-industry linkages to promote CSR education in the country. Since the issue of CSR and business ethics has the direct bearing on business and management domain, the paper has explored the syllabi of business schools. The study— based on a descriptive approach—sought to draw out a perspective on the content and pedagogy of the BE and CSR module in Nepali varsities. Encompassing the existing Nepali universities and/or the business schools under their fold, the study discovered that Tribhuvan University, the only central and national university of Nepal, has offered more BE and CSR contents either as a separate, independent module or as an integral part of other related subjects in a larger number of bachelors and masters programmes. Yet, there is a need to specify and ameliorate pedagogical arrangements in most of the universities in Nepal. Since BE and CSR are relatively young modules, the findings should prove instrumental for Nepali universities to formulation of curricular plans and strategies vis-à-vis foreign business schools in the days to come.